2020
DOI: 10.1136/gpsych-2020-100237
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia with and without obsessive-compulsive symptoms: a comparative analysis of performance on trail making test and disability on WHODAS

Abstract: BackgroundPresence of obsessive-compulsive symptoms (OCS) affects performance on tests of some cognitive functions, such as the trail making test (TMT), and may affect the level of disability in schizophrenia (SZ).AimsThe aim of the present study was to compare performance on TMT and disability on WHO Disability Assessment Schedule (WHODAS) in persons with SZ with and without OCS in a cross-sectional study.MethodsPersons with SZ (n=200) fulfilling DSM-V (Diagnostic and Statistical Manual) diagnostic criteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…1,25 Moreover, patients with schizophrenia and OCS seem to have more severe psychotic and depressive symptoms and lower social functioning and disability. 11,27,32,33 However, some recent studies have suggested that the impact of schizophrenia may vary depending on the stage of schizophrenia, with early schizophrenia having a shielding effect and chronic schizophrenia having a deleterious effect. 34 In this study, delusions and OCS were found to have a positive correlation, supporting the view that these reflect a manifestation of over-valued ideas lying on a continuum of obsessional doubts to delusional certainty, suggesting a common underlying mechanism that may be related to a decreased capacity to inhibit behaviors or thoughts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,25 Moreover, patients with schizophrenia and OCS seem to have more severe psychotic and depressive symptoms and lower social functioning and disability. 11,27,32,33 However, some recent studies have suggested that the impact of schizophrenia may vary depending on the stage of schizophrenia, with early schizophrenia having a shielding effect and chronic schizophrenia having a deleterious effect. 34 In this study, delusions and OCS were found to have a positive correlation, supporting the view that these reflect a manifestation of over-valued ideas lying on a continuum of obsessional doubts to delusional certainty, suggesting a common underlying mechanism that may be related to a decreased capacity to inhibit behaviors or thoughts.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 25 Moreover, patients with schizophrenia and OCS seem to have more severe psychotic and depressive symptoms and lower social functioning and disability. 11 , 27 , 32 , 33 However, some recent studies have suggested that the impact of schizophrenia may vary depending on the stage of schizophrenia, with early schizophrenia having a shielding effect and chronic schizophrenia having a deleterious effect. 34 …”
Section: Discussionmentioning
confidence: 99%
“…The trail marking test (TMT) was firstly used in 1944 for America army individual intelligence assessment [ 22 ]. Nowadays, it is widely employed as a diagnostic tool for visual attention and executive functioning and the processing speed for neuropsychological diseases [ 23 , 24 ]. It consists of two parts in which the subject is instructed to connect a set of 25 circles containing numbers (Part A) or numbers and letters (Part B) arrayed pseudorandomly on a letter-size sheet of paper as fast as possible while still maintaining accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…The scoring criteria are the time taken to complete TMT-A and TMT-B, as well as the interference amount (TMT-B time consumption minus TMT-A time consumption) [ 17 ]. This tool is commonly used for diagnosing visual attention, executive function, and processing speed in neuropsychological diseases [ 18 , 19 ]. ADL.…”
Section: Interventionsmentioning
confidence: 99%